Identification of the cereal leafminer (Syringopais temperatella) tolerance sources in a spring barley core collection and their genome-wide genetic dissection - Adel H. Abdel-Ghani; Rasha A. Tarawneh; Saddam A. Al-Dalain; Yacoub Emeel Hijazeen; Mahmud A. Duwayri; Soud Abbadi; Yehya Alattal; Saed J. Owais; Sobhia Saifan; Huda Hazim Al-Taae; Benjamin Kilian; Kerstin Neumann (Genetic Resources and Crop Evolution, 2026)

Correction to: Oxytocin Receptor Expression in Hair Follicle Stem Cells: A Promising Model for Biological and Therapeutic Discovery in Neuropsychiatric Disorders - Sareh Pandamooz; Mohammad Saied Salehi; Benjamin Jurek; Carl-Philipp Meinung; Negar Azarpira; Mehdi Dianatpour; Inga D. Neumann (Stem Cell Reviews and Reports, 2026)

On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Correction to: The context‑dependent role of the Na+/Ca2+‑exchanger (NCX) in pancreatic stellate cell migration - Thorsten Loeck; Micol Rugi; Luca Matteo Todesca; Paulina Kalinowska; Benjamin Soret; Ilka Neumann; Sandra Schimmelpfennig; Karolina Najder; Zoltán Pethő; Valerio Farfariello; Natalia Prevarskaya; Albrecht Schwab (Pflügers Archiv - European Journal of Physiology, 2024)

Oxytocin Receptor Expression in Hair Follicle Stem Cells: A Promising Model for Biological and Therapeutic Discovery in Neuropsychiatric Disorders - Sareh Pandamooz; Mohammad Saied Salehi; Benjamin Jurek; Carl-Philipp Meinung; Negar Azarpira; Mehdi Dianatpour; Inga D. Neumann (Stem Cell Reviews and Reports, 2023)

The context-dependent role of the Na+/Ca2+-exchanger (NCX) in pancreatic stellate cell migration - Thorsten Loeck; Micol Rugi; Luca Matteo Todesca; Paulina Kalinowska; Benjamin Soret; Ilka Neumann; Sandra Schimmelpfennig; Karolina Najder; Zoltán Pethő; Valerio Farfariello; Natalia Prevarskaya; Albrecht Schwab (Pflügers Archiv - European Journal of Physiology, 2023)
Pancreatic stellate cells (PSCs) that can co-metastasize with cancer cells shape the tumor microenvironment (TME) in pancreatic ductal adenocarcinoma (PDAC) by producing an excessive amount of extracellular matrix. This leads to a TME characterized by increased tissue pressure, hypoxia, and acidity. Moreover, cells within the tumor secrete growth factors. The stimuli of the TME trigger Ca 2+ signaling and cellular Na + loading. The Na + /Ca 2+ exchanger (NCX) connects the cellular Ca 2+ and Na + homeostasis. The NCX is an electrogenic transporter, which shuffles 1 Ca 2+ against 3 Na + ions over the plasma membrane in a forward or reverse mode. Here, we studied how the impact of NCX activity on PSC migration is modulated by cues from the TME. NCX expression was revealed with qPCR and Western blot. [Ca 2+ ] i , [Na + ] i , and the cell membrane potential were determined with the fluorescent indicators Fura-2, Asante NaTRIUM Green-2, and DiBAC 4 (3), respectively. PSC migration was quantified with live-cell imaging. To mimic the TME, PSCs were exposed to hypoxia, pressure, acidic pH (pH 6.6), and PDGF. NCX-dependent signaling was determined with Western blot analyses. PSCs express NCX1.3 and NCX1.9. [Ca 2+ ] i , [Na + ] i , and the cell membrane potential are 94.4 nmol/l, 7.4 mmol/l, and − 39.8 mV, respectively. Thus, NCX1 usually operates in the forward (Ca 2+ export) mode. NCX1 plays a differential role in translating cues from the TME into an altered migratory behavior. When NCX1 is operating in the forward mode, its inhibition accelerates PSC migration. Thus, NCX1-mediated extrusion of Ca 2+ contributes to a slow mode of migration of PSCs.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Auf dem Weg zu besseren Wasserstand-Durchfluss-Beziehungen - Henning Oppel; Juliane Neumann; Benjamin Mewes; Alexander Hartung (WASSERWIRTSCHAFT, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2022)
Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGA t A t genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge value for wheat breeding, the tetraploid GGA t A t genepool is largely neglected. Understanding the population structure, native distribution range, intraspecific variation of the entire tetraploid GGA t A t genepool and its domestication history would further its use for wheat improvement. The paper provides the first comprehensive survey of genomic and cytogenetic diversity sampling the full breadth and depth of the tetraploid GGA t A t genepool. According to the results obtained, the extant GGA t A t genepool consists of three distinct lineages. We provide detailed insights into the cytogenetic composition of GGA t A t wheats, revealed group- and population-specific markers and show that chromosomal rearrangements play an important role in intraspecific diversity of T. araraticum . The origin and domestication history of the GGA t A t lineages is discussed in the context of state-of-the-art archaeobotanical finds. We shed new light on the complex evolutionary history of the GGA t A t wheat genepool and provide the basis for an increased use of the GGA t A t wheat genepool for wheat improvement. The findings have implications for our understanding of the origins of agriculture in southwest Asia.

Does Biochar Particle Size, Application Rate and Irrigation Regime Interact to Affect Soil Water Holding Capacity, Maize Growth and Nutrient Uptake? - Eric Oppong Danso; Francis Monnie; Stephen Abenney-Mickson; Emmanuel Arthur; Edward Benjamin Sabi; Mathias Neumann Andersen (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2021)

The Indo‐European flyway: Opportunities and constraints reflected by Common Rosefinches breeding across Europe - Simeon Lisovski; Roland Neumann; Tomas Albrecht; Pavel Munclinger; Markus P. Ahola; Silke Bauer; Jaroslav Cepak; Thord Fransson; Sven Jakobsson; Tuomo Jaakkonen; Petr Klvana; Cecilia Kullberg; et al. (Journal of Biogeography, 2021)
Aim The configuration of the earth's landmasses influences global weather systems and spatiotemporal resource availability, thereby shaping biogeographical patterns and migratory routes of animals. Here, we aim to identify potential migratory barriers and corridors, as well as general migration strategies within the understudied Indo‐European flyway. Location Europe, Central Asia. Major taxon studied Common rosefinches. Methods We used a combination of theoretical optimization modelling and empirical tracking of Common Rosefinches ( Carpodacus erythrinus ) breeding across a large latitudinal gradient in Europe. First, we identified optimal migration routes driven by wind and resource availability along the Indo‐European flyway. Second, we tracked rosefinches from five breeding populations using light‐level geolocators. Finally, we compared to what extent empirical tracks overlapped with the modelled optimal routes. Results In autumn, theoretical wind driven migration routes formed a broad‐front corridor connecting Europe and the Indian Subcontinent while the theoretical resource driven routes formed a distinct north‐south divide. The latter pattern also reflected the rosefinch tracks with all but the most southerly breeding birds making a northern detour towards non‐breeding sites in Pakistan and India. In spring, the resource availability model predicted a similar migratory divide, however, the southern route seemed relatively more favourable and closely matched with the optimal wind driven migration routes. Spring tracking data showed larger overlap with the modelled wind driven migration routes compared to the resource driven routes. Main conclusions Optimal wind and resource driven migration routes along the Indo‐European flyway are seasonally specific and to a large extend do not overlap with one another. Under these conditions, migratory birds adopt seasonally distinct migration strategies following energy minimization strategy in autumn, driven by resource availability, and time minimizing strategy in spring, driven by wind conditions. Our optimal migration models can be applied worldwide and used to validate against empirical data to explain large‐scale biogeographic pattern of migratory animals.

Auswirkungen des Klimawandels auf das Grundwasser und die Wasserversorgung in Süddeutschland - Ronja Fliß; Christof Baumeister; Thomas Gudera; Mario Hergesell; Benjamin Kopp; Jörg Neumann; Miriam Posselt (Grundwasser, 2021)
Zusammenfassung Für die öffentliche Trinkwasserversorgung in Süddeutschland wird größtenteils Grund- und Quellwasser genutzt. Der Kenntnis über die Entwicklung des Bodenwasserhaushalts und insbesondere der Grundwasserneubildung kommt somit eine große Bedeutung zu. Im Rahmen der Kooperation KLIWA (Klimaveränderung und Konsequenzen für die Wasserwirtschaft, www.kliwa.de ) wurde die Entwicklung des Bodenwasserhaushaltes und der Grundwasserneubildung aus Niederschlag für den Zeitraum von 1951 bis 2019 für die Länder Baden-Württemberg, Bayern, Hessen und Rheinland-Pfalz mit dem Bodenwasserhaushaltmodell GWN-BW modelliert. Seit Ende der 1980er-Jahre zeigt sich ein Anstieg der mittleren jährlichen Temperatur in Süddeutschland. Die jährlichen Niederschlagssummen haben sich in der jüngeren Vergangenheit (seit 2003) reduziert und somit eine deutliche Verringerung der Grundwasserneubildung aus Niederschlag bewirkt. Gleichzeitig ist eine Zunahme des Trockenheitsindex (Anzahl an Tagen mit Füllung des Bodenwasserspeichers < 30 % der nutzbaren Feldkapazität) zu erkennen. Häufiger werdende und länger anhaltende Trockenperioden stellen auch die Wasserwirtschaft zunehmend vor Herausforderungen und bedürfen der frühzeitigen Entwicklung von Handlungsoptionen, z. B. auf der Basis des hier vorgestellten „Trockenwetterdargebots“, um Nutzungskonflikte zu entschärfen.

Polyphase enrichment and redistribution processes in silver-rich mineral associations of the hydrothermal fluorite-barite-(Ag-Cu) Clara deposit, SW Germany - Maximilian F. Keim; Benjamin F. Walter; Udo Neumann; Stefan Kreissl; Richard Bayerl; Gregor Markl (Mineralium Deposita, 2019)

Diversity of germination and seedling traits in a spring barley (Hordeum vulgare L.) collection under drought simulated conditions - Adel H. Abdel-Ghani; Kerstin Neumann; Celestine Wabila; Rajiv Sharma; Sidram Dhanagond; Saed J. Owais; Andreas Börner; Andreas Graner; Benjamin Kilian (Genetic Resources and Crop Evolution, 2015)

Differential influenza H1N1-specific humoral and cellular response kinetics in kidney transplant patients - Vinay Rambal; Karin Müller; Chantip Dang-Heine; Arne Sattler; Mikalai Dziubianau; Benjamin Weist; Si-Hong Luu; Alexandra Stoyanova; Peter Nickel; Andreas Thiel; Avidan Neumann; Brunhilde Schweiger; et al. (Medical Microbiology and Immunology, 2014)

Identification of transcripts from a subtraction library which might be responsible for the mild phenotype in an intrafamilially variable course of Duchenne muscular dystrophy - Marco Sifringer; Birgit Uhlenberg; Stefanie Lammel; Rita Hanke; Benjamin Neumann; Arpad von Moers; Ina Koch; Astrid Speer (Human Genetics, 2004)